Tinjauan Hukum Islam Terhadap Penjualan Pakaian Di Toko Matahari - Firda Najwatunnissa; Indriyani; Muhibban (CV. ITTC INDONESIA, 2025)
The clothing industry in Indonesia, including the products sold at Matahari Department Store, has been growing rapidly by offering a wide variety of fashion choices. However, as a country with a Muslim-majority population, it is important to assess the extent to which the clothing products sold adhere to Islamic legal principles, such as halal compliance, modesty, and conformity to the requirements of covering the aurat. This research aims to examine the Islamic legal perspective on the clothing sold at Matahari by focusing on aspects of design, materials, and product marketing.The methodology employed in this research is a qualitative approach with descriptive analysis, involving a review of Islamic legal literature and observations of the clothing products sold in the store. The findings reveal that most of the clothing at Matahari meets the principles of modesty and halal compliance. However, some products still fall short of Sharia requirements, such as clothing that is overly tight or transparent.The study concludes that although the majority of products fulfill Sharia criteria, there is still room for improvement in design and material selection to better align with Islamic legal principles. Thus, this research provides an important contribution to understanding the relationship between the retail fashion industry and Islamic law while offering guidance for Muslim consumers in selecting clothing that complies with Sharia.